A compendium of DNA-binding specificities of transcription factors in Pseudomonas syringae - Ligang Fan (Nature Portfolio, 2020)
The authors set out to identify binding motifs for all 301 transcription factors of a plant pathogenic bacterium, Pseudomonas syringae, using HT-SELEX. They successfully identify binding motifs for 100 transcription factors, infer their binding sites on the genome, and validate the predicted interactions and functions.